Understanding memorable tourism experiences and revisit intention from destination service quality - Laela, Ela (Universitas Tarumanagara, 2024)
This research explores the relationship between destination service quality, memorable tourism experiences, and revisit intention. The population of this study were tourists in Bandung, Jakarta, Malang, Yogyakarta, Lombok, and Bali. A sample of 300 respondents was involved in the study. The method used in this research is a survey with structural equation modeling analysis techniques. The results revealed that destination service quality affects memorable tourism experiences and revisit intention. In addition, a memorable tourism experience affects revisit intention. This study found that memorable tourism experience partially mediates the relationship between destination service quality and revisit intention. Penelitian ini mengeksplorasi hubungan antara destination service quality, memorable tourism experience, dan revisit intention. Populasi penelitian ini adalah wisatawan Bandung, Jakarta, Malang, Yogyakarta, Lombok, dan Bali. Sampel sebanyak 300 responden dilibatkan dalam penelitian. Metode yang digunakan dalam penelitian ini adalah survei dengan teknik analisis Structural Equation Modeling. Hasil penelitian mengungkap bahwa destination service quality berpengaruh terhadap memorable tourism experience dan revisit intention. Selain itu, memorable tourism experience berpengaruh terhadap revisit intention. Penelitian ini menemukan bahwa memorable tourism experience berperan sebagai mediasi parsial dalam hubungan destination service quality terhadap revisit intention.